HE EFFECTIVENESS OF THE SAKINAH HERITAGE PROGRAM IN 2019 IN THE OFFICE OF RELIGIOUS AFFAIRS, TAMPAN DISTRICT, PEKANBARU CITY - Amalia Fiddaraini; Zaili Rusli (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
The high rate of divorce in Pekanbaru City is a big task that must be completed by the Ministry of Religion. Therefore the Pusaka Sakinah Program is needed to reduce the divorce rate which is still high in Pekanbaru City. The purpose of this study was to determine the effectiveness and inhibiting faktors of the Pusaka Sakinah Program, using qualitative research methods. The results of this study indicate that the Sakinah Heritage Program received a positive response by the community in its implementation, but this program has not run optimally considering that there are still several obstacles and obstacles that affect the sustainability, consistency, and active participation of the community in participating in activities made by the KUA during realize this Pusaka Sakinah program.